Length at age of Atlantic cod (Gadus morhua) around the coast of Iceland over the period 1985 - 2016 - Katrín Hulda Gunnarsdóttir 1995- (2017)
Length-at-age of cod around Iceland has been documented by the Marine Institute of Iceland (MRI) since 1985. Mapping out that data made it possible to see whether the length of the cod had increased or decreased through time as well if there was a difference in size between regions. Mapping was done using Akima interpolation of length data from MRI’s annual research surveys in the program R. Results indicated that the size of fish had decreased slightly in each age group represented. The reasons for the decline are unknown but can likely be linked to changes in ocean temperatures. Fish are also larger south of Iceland than north of the country. The difference may be a result of ocean temperatures being higher south of Iceland than north of Iceland. Lengd þorska við ákveðinn aldur umhverfis Ísland hefur verið skráð af Hafrannsóknarstofnun Íslands (HAFRÓ) síðan 1985. Kortlagning á þeim gögnum gerði mögulegt að sjá hvort lengd þorska við landið hefði minnkað eða aukist á tímabilinu 1985-2016 og hvort stærðarmunur væri á milli landshluta. Kortlagning var gerð með því að nota Akima aðferð við framreiknun á upprunalegu lengdargögnunum frá HAFRÓ. Notast var við forritið R. Í ljós kom að stærð fiska á ákveðnum aldri hefur minnkað örlítið í öllum aldurshópum. Ástæður þess eru ekki þekktar en líklega má tengja þær breytingum í hitastigi. Einnig kom í ljós að fiskar eru stærri fyrir sunnan en norðan land. Þann stærðarmun má hugsanlega tengja við að hitastig sjávar sem er hærra fyrir sunnan en norðan land.